If a, b, c are all nonzero and a + b + c = 0, prove that


If $a, b, c$ are all nonzero and $a+b+c=0$, prove that $\frac{a^{2}}{b c}+\frac{b^{2}}{c a}+\frac{c^{2}}{a b}=3$.



$a+b+c=0 \Rightarrow a^{3}+b^{3}+c^{3}=3 a b c$

Thus, we have:

$\left(\frac{a^{2}}{b c}+\frac{b^{2}}{c a}+\frac{c^{2}}{a b}\right)=\frac{a^{3}+b^{3}+c^{3}}{a b c}$

$=\frac{3 a b c}{a b c}$



Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now